Environmental Sustainability in Indonesia: The Impact of Islamic Financial Development, Economic Growth, Poverty, Population on Environmental Quality - Siregar, Suci Wulandari; Hasbi (Universitas Muhammadiyah Yogyakarta, 2025)
Environmental Quality in Indonesia faces major challenges due to the worsening phenomenon of environmental degradation, driven by rapid population growth, uncontrolled urbanization, and intense economic expansion. Air quality in many regions is declining along with increasing industrial activities, energy consumption, and excessive use of natural resources. This study analyzes the impact of Islamic Financial Development (IFD), economic growth (GDP), poverty rate (POV), and population (POP) on environmental quality, with a focus on air quality. By adopting the Panel Vector Error Correction Model (PVECM) method. Panel data from 34 provinces in Indonesia was comprehensively analyzed to understand short- and long-term dynamics. The results show that IFD contributes positively to environmental quality in the long term through the financing of sustainable projects, while GDP exerts negative pressure in the short term but turns positive in the long term in regions with strong environmental policies. Poverty reductions significantly improve environmental quality in the long term, while population growth consistently puts negative pressure on air quality. This study emphasizes the importance of effective environmental policies and investments in green technologies that are not only focused on urban centers, but also applied evenly throughout the country to ensure the sustainability of environmental quality throughout Indonesia.